Tirukkaḻippālait tiruppatikaṅkaḷ (Adhinam publications, 1975)
History of the Saivite temple at Tirukkaḻippālai, South Arcot District, Tamil Nadu; includes a selection of hymns from Tamil Saivite devotional literature.